Pengaruh Time Budget Pressure dan Risiko Audit terhadap Kualitas Audit - Fitri Nuraeni; Ali Rahman Reza Zaputra (Ekonomis: Journal of Economics and Business, 2026)
The purpose of this study is to analyze the effect of time budget pressure and audit risk on audit quality, using a case study of a Public Accounting Firm (PAF) in Bandung. This study uses a quantitative approach with a causal-comparative design and survey method. A sample of 40 auditors was selected using a purposive sampling technique from 8 active FAFs in Bandung City. Data were collected through a closed questionnaire and analyzed using multiple linear regression. The results show that the time budget pressure variable has no significant effect on audit quality, while the audit risk variable has a significant positive effect on audit quality. Simultaneously, both variables have a significant effect on audit quality. This finding confirms that auditors tend to increase their thoroughness when facing high audit risk, but time pressure does not directly reduce work quality if supported by adequate systems and experience.